Experimental Study of CCS Application in Late Water-Driven Reservoirs - Jiang, Yan; Hu, Shaobin (International Journal of Natural Resources and Environmental Studies, 2025)
Under the background of “double carbon” target, injection of CO2 into oil reservoirs has attracted a lot of attention as a key technology pathway to enhance crude oil recovery and realize geological storage of CO2. In the past decade, CCUS (Carbon Capture, Utilization and Storage) technology has become a research hotspot in the process of global energy transition by virtue of its dual benefits of carbon reduction and production increase in the oil and gas industry. Currently, most of the major oilfields in China have been under water-driven development for a long period of time, and they are facing the problem of high and stable production, and their development programs need to be adjusted urgently. Based on the above situation, this study carried out indoor oil drive physical simulation experiments, aiming to compare the effect of CO2 oil drive after water drive. The experimental results show that CO2-assisted oil drive is effective, the recovery rate from the test basis and technical reference, is expected to help the oilfield to meet the energy demand at the same time, and effectively promote the realization of the “double carbon” goal.